Italian readers of Il Giornalino della Domenica and Il Passerotto between the Great war and the Fiume endeavour - Fava, Sabrina (Array, 2019)
Early 20th-century children’s magazines chart fundamental steps in the development of children’s literature, both in literary production itself, and the ways in which young readers were taught to read. This paper explores the points of view of the literary text and of actual readers in the weekly Il Giornalino della Domenica and the monthly Il Passerotto, with reference to the topics of interventionism and irredentism that characterised the thoughts and dreams of many subscribers to the magazines. Until the First World War, the unification of the irredentist regions took the shape of fantastic and humorous accounts, but the apex of irredentism was reached with the Fiume endeavour. This long-held pre-war dream gave voice to the rebelliousness of a whole generation of young people who had grown up yearning to see the epic of the Risorgimento finally laid to rest. As young adults, they were convinced that they could convey the outcome of this to the two magazines’ new generation of young readers. Analysis of the two magazines enables us to reconstruct the continuities and changes that shaped the intellectual growth of child readers and anticipate the choices they would make as adults, some of which would have dramatic consequences.